PEMANFAATAN TUMBUHAN SAGU (Metroxylon sagu) OLEH MASYARAKAT DI KECAMATAN CANDI LARAS SELATAN KABUPATEN TAPIN PROVINSI KALIMANTAN SELATAN - Abdi Fithria; Kissinger Kissinger; Siti Syifa (Universitas Lambung Mangkurat, 2026)
The sago plant is a palm-type plant that grows in wet tropical areas, namely in freshwater areas, swamps, along river flows and around water sources. The productivity of sago plants is higher than other carbohydrate-producing plants, this is another alternative in the consumption of carbohydrates to replace rice. The potential area of sago plants in Indonesia is very large but the utilization of this plant by the community is still not optimal which is estimated to be only 15-20%. This study aims to analyze the utilization and sale distribution of sago plants (Metroxylon sago) in the community in Candi Laras Selatan District, Tapin Regency, South Kalimantan Province. Data collection to analyzethe utilization of sago plants using interviews to the community using purposive sampling method. Analysis of the distribution of sago plants sales was carried out by field observation and taking coordinate points where sago grows using purposive sampling method. Primary data was obtained based on results of interviews from the community and direct data collection in the field regarding the coordinates of the growing point of the sago plant. The utilization of sago plants in Candi Laras Selatan is that the trunks are sold directly to the owners of sago or sago starch processing factories, the trunks are sold directly to the owners of duck livestock, and the leaves of sago plants are processed into house roofs or livestock kandangan roofs. Sago plant producers in Candi Laras Selatan Subdistrict are Sungai Rutas, Sungai Rutas Hulu, Pabaungan Hulu and Marampiau. Village with sales distribution to the Marampiau Hilir, Danau Panggang, Babirik Hulu, and Kandangan areas.